Do Birds of a Feather Always Flock Together? Assessing Differences in Group and Individual Zoo Enclosure Usage by Comparing Commonly Available Methods - Heather McConnell; James Brereton; Tom Rice; Paul Rose (Journal of Zoological and Botanical Gardens, 2022)
Data on zoo enclosure usage provide meaningful evaluation of husbandry and welfare but for social species, group-level data may not capture individual occupancy preferences. Determining zone occupancy using group data may give an inaccurate assessment of enclosure suitability for each individual. We compared three formulae (traditional and modified Spread of Participation Index and Electivity Index) to determine how estimations of space usage compare between individuals and their group overall. Two flamingo flocks at two zoos were sampled with enclosures separated into discrete zones. Counts of where each bird in the flock was located at each minute of sampling were compared against the number of minutes that randomly selected individual flamingos spent in each zone. Overall, there was little difference in preferred zone occupancy when flock data were compared to individual data. Group data suggested that flamingos were more consistent in their enclosure usage, with individual data showing wider overall usage of enclosures. Individual Electivity Index (EI) values suggested zone underuse whereas group EI suggested zone overuse. As a proxy for welfare measurement, we recommend both group-level and individual monitoring of space use to provide a complete picture of how individuals within a social group occupy their space and choose where to be.